Asymmetrical Diaromatic Guanidinium/2-Aminoimidazolinium Derivatives: Synthesis and DNA Affinity - ROZAS, ISABEL (My University, 2009)
In this paper we report the synthesis of three families of new amidine?based aromatic derivatives as potential DNA minor groove binding agents for the treatment of cancer. The preparation of mono?guanidine, mono?2?aminoimidazoline and asymmetric diphenyl guanidine/2?aminoimidazoline derivatives (compounds 1a,b,c to 8a,b,c) is presented. The affinity of these substrates and of a family of mono? and bis?isoureas (previously prepared in Rozas? laboratory) for DNA was evaluated by means of DNA thermal denaturation measurements. In particular, compounds 2c, 5c, 6c, 7c, and 8c were found to bind strongly both to natural DNA and to Adenine-Thymine oligonucleotides, showing a preference for the Adenine-Thymine base pairs sequences.
PUBLISHED
Keywords: DNA